SISTEM INFORMASI PEMESANAN MAKANAN DAN MINUMAN PADA CAFE RACIK KOPI MEDAN BERBASIS WEB - H.P.Pangondian Lumbantoruan; Ramen A Purba (Cendekia Madani Nusantara, 2025)
This research aims to build a Web-Based Food and Beverage Ordering Information System for Cafe Racik Kopi Medan. In addition, this research also seeks to develop an application that can provide sales reports for Cafe Racik Kopi Medan. The problem at Cafe Racik Kopi Medan has been ongoing because the system is still manual. Therefore, a system was built that can serve as a solution to those problems. The methods used to design online sales are the observation method, library method, system implementation, system analysis, and system design. This program was created using PHP and MySQL as the database, and it is designed as a fast, practical, and satisfying sales system for the community.